Analisis Markov Chain terhadap Persediaan: Studi Kasus pada CV Sinar Bahagia Group - Haryadi Sarjono; Edwin Edwin; Himawan Sentosa; Frendy Bong (Binus Business Review, 2011)
Supply is one of the most important factors for the company, but there are still so many companies who don’t understand about how to monitoring their supplies so there will be not too much or too little supplies for them to manage. Some of the important things are to know how many supplies that a company should prepare to fulfill the needs of supply for the next period. This essay is aimed to investigate whether there was a shift/moving towards the supplies and the factor, which trigger the moving, how many supplies that the company should have and the cost that they have to pay to fulfill the supplies. The result shows that there was a moving of supplies, which has been cause by some factors. The kind of research that being used is a descriptive research, with a quantitative data. And the methods that being used is the case study, The point of this research is because of the moving of supplies that has been caused by the age of the supplies, the company have to calculate how many supplies that they should have to fulfill the needs of the next period.